Mathematics education and teaching materials in Lithuania - Būdienė, Virginija; Stričkienė, Marytė (Lietuvos matematikos rinkinys, 1999)
This paper addresses issues in the use of new generation of teaching materials in mathematics education in Lithuania. The principles of current policy on textbook writing and experimental implementation is examined. By reflecting on teacher's attitudes survey assumption is made on the influence of new textbooks on mathematics instruction.